Treating Malignancy: Four-Year Experience in Internal Medicine Department, BIRDEM General Hospital (BIRDEM Medical Journal, 2017)
Background: Cancer prevalence in diabetic patients in Bangladesh seems to be increasing as case detection of both diseases are far more than before. Till date no statistical data of diabetic patients with malignancy is available in Bangladesh. Treating both diabetes and malignancy in the same patient is challenging and sometimes requires multidisciplinary support. For such cases BIRDEM General Hospital offers supportive facilities including intensive care, chemotherapy, surgical intervention and oncology day care.Methods: This cross-sectional, observational study was carried out from January 2012 to June 2016 which included cancer patients irrespective of their diabetic status admitted in Internal Medicine Department of BIRDEM General Hospital. With prior informed consent of the patients, data were collected and statistical analysis was done using professional SPSS version 17.0 windows based program.Results: Total number of cancer patients was 114, whose diagnoses were confirmed by histopathological evidence (biopsy/FNAC), radiology reports and cancer markers, as appropriate. Among them 64 (56.1%) were male and 50 (43.9%) were female patients. Age of most of the patients was between 41-60 years (65, 57%). Mean age was 55.16 years in diabetic group and 44.47 years in non-diabetic group. Glycemic status revealed that most of the patients were diabetic (80, 70.2%). Among other co-morbid conditions, hypertension and ischemic heart disease were predominant (17 and 9 cases respectively). Prevalence of more than one comorbidites were marked in the diabetic group (33 cases, p value >0.001). Twenty one categories of malignancies were diagnosed during this study period. Majority of cases were lymphoma (21,18.4%), carcinoma breast (17,14.9%), carcinoma uterus and/or cervix (13,11.4%) and leukaemia (10,8.8%). Common clinical features included palpable lump (21,18.4%), lymphadenopathy (16,14%), anaemia (9,7.9%) and pain (8,7%). The number of patients presenting with multiple signs/symptoms were also significant (32,28.1%). Most patients were treated with chemotherapy (54,47.4%). Many cases warranted a combined approach (46,40.4%). Treatment response showed good response in 57(50%) cases. In 16 patients (14%) condition deteriorated and death occurred in 8 cases (7%). Even after repeated and empathic counseling we lost follow up of 15 cases (13.2%).Conclusion: The scenario becomes complicated when a diabetic patient develops malignancy and vice versa. Complications can arise from either spectrum of the diseases. Managing such cases are often challenging and require multi-disciplinary support. Management outcome of these cases so far in Internal Medicine Department, BIRDEM General Hospital shows a promising future.Birdem Med J 2016; 6(2): 107-111